2011
DOI: 10.1371/journal.pone.0018603
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Thermoregulatory Tactics in Lacustrine Brook Charr, Salvelinus fontinalis

Abstract: The need to vary body temperature to optimize physiological processes can lead to thermoregulatory behaviours, particularly in ectotherms. Despite some evidence of within-population phenotypic variation in thermal behaviour, the occurrence of alternative tactics of this behaviour is rarely explicitly considered when studying natural populations. The main objective of this study was to determine whether different thermal tactics exist among individuals of the same population. We studied the behavioural thermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 43 publications
3
53
2
Order By: Relevance
“…The former behaviour simulated attack rate or feeding bouts in time budget experiments (Marchand et al, 2003) when fish swam rapidly to eat at the surface and then returned to deep water. Previous telemetry studies suggested that the latter behaviour, equivalent to our step change experiments, could be adopted by lacustrine brook trout as a response to summer lake warming (Bertolo et al, 2011;Goyer et al, 2014). Although cyclic oscillations are mainly presented as illustrative examples, we provide quantitative theoretical predictions of the maximum duration of sporadic excursions.…”
Section: Theoretical Predictions Of Maximum Excursion Durationmentioning
confidence: 58%
See 3 more Smart Citations
“…The former behaviour simulated attack rate or feeding bouts in time budget experiments (Marchand et al, 2003) when fish swam rapidly to eat at the surface and then returned to deep water. Previous telemetry studies suggested that the latter behaviour, equivalent to our step change experiments, could be adopted by lacustrine brook trout as a response to summer lake warming (Bertolo et al, 2011;Goyer et al, 2014). Although cyclic oscillations are mainly presented as illustrative examples, we provide quantitative theoretical predictions of the maximum duration of sporadic excursions.…”
Section: Theoretical Predictions Of Maximum Excursion Durationmentioning
confidence: 58%
“…Brook charr followed with radiotelemetry spent most of their time in the metalimnion, which corresponds to their preferred temperature (i.e. depth <8 m; Bertolo et al, 2011;Goyer et al, 2014), and rarely entered the hypolimnion. Considering a cruising speed of two body lengths per second (Bjornn and Reiser, 1991;Rouleau et al, 2010;Castro-Santos et al, 2013), a brook charr of 300 mm total length could reach the surface within 15 s. Extrapolating our experimental results to natural populations, we can predict excursion times into the epilimnion according to the thermal constraints of the species under study (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robinson and Parsons 2002). Thus, temperature adaptations have had less focus as the thermal gradient is low along these upper-water resource axes, although thermal microhabitat differences can have significant importance (Bertolo et al 2011). There is an increasing awareness of specifically adapted deep-water morphs of postglacial fishes, both along the benthic zone (e.g.…”
Section: Introductionmentioning
confidence: 99%